The tools ebook 5 tools to help you find courage, creativity, and willpower—and inspire you to live life in forward motion. - Stutz, Phil (2012)
NEW YORK TIMES BESTSELLER • Change can begin right now. Learn to bring about dynamic personal growth using five uniquely effective tools—from psychotherapist Barry Michels and psychiatrist Phil Stutz, subject of the Netflix documentary Stutz. “These tools are emotional game changers. They do nothing less than deliver you to your best and most powerful self.”—Kathy Freston, author of Quantum Wellness   How long does therapy take? The Tools offers a solution to the biggest complaint patients have about therapy: the interminable wait for change to begin. The traditional therapeutic model sets its sights on the past, but psychiatrist Phil Stutz and psychotherapist Barry Michels employ an arsenal of techniques—“the tools”—that allow patients to use their problems as levers that access the power of the unconscious and propel them into action. Suddenly, through this transformative approach, obstacles become new chances—to find courage, embrace discipline, develop self-expression, deepen creativity.   A dynamic, results-oriented practice, The Tools aims to deliver relief from persistent problems and restore control and hope right away. Every day presents challenges—big and small—that the tools transform into opportunities to bring about bold and dramatic change in your life. Stutz and Michels teach you how to:   • Get Unstuck : Master the things you are avoiding and live in forward motion. • Control Anger : Free yourself from out-of-control rage and never-ending grudges. • Express Yourself : Learn the secret of true confidence and find your authentic voice. • Combat Anxiety : Stop obsessive worrying and negative thinking. • Find Discipline : Activate willpower and make the most of every minute.   With The Tools, Stutz and Michels allow you to realize the full range of your potential. Their goal is nothing less than for your life to become exceptional—exceptional in its resiliency, in its experience of real happiness, and in its understanding of the human spirit.